Gas molecule adsorption on twisted nanographene C96H36 derivative: A theoretical study. (March 2019) - Cui, Cheng-Xing; Tian, Yuan; Zhang, Yu-Ping; Qu, Ling-Bo; Lan, Yu
Abstracts: Twisted C96 H36, a newly synthesized nanographene, may have distinct properties from those of planar graphene. The adsorption behaviors of H2, CO, NO, NH3, SO2, and HCHO on the surface of C96 H36 derivative, which was labelled asC96, were systematically investigated by computational methods. The adsorption behaviors of 1–20 formaldehyde molecules onC96 were calculated to reveal potential uses ofC96 . The results indicate that these molecules could be physically absorbed on the surface ofC96 with absorption energies in the range 0.5–5.5 kcal mol −1 . The calculated HOMO-LUMO energy gap also showed thatC96 could act as a potential gas sensor for O2 and SO2 . When one formaldehyde molecule is absorbed, it prefers to locate at the edge of the distorted moiety ofC96 . A second formaldehyde also prefers to be absorbed at another edge position of the distorted moiety ofC96 . The results show that the absorption energies for the third to twelfth formaldehyde molecules are concentrated at 5 kcal mol −1, which indicates that more formaldehyde molecules could be absorbed ontoC96, but a limit of 20 formaldehyde molecules was calculated. Graphical abstract: